I hear but I don't see you: Interacting over phone reduces the accuracy of perceiving affiliation in the other. (December 2018) - Sadikaj, Gentiana; Moskowitz, D.S.
Abstract: In-person interactions are characterized by better psychological and interpersonal outcomes than technology-mediated interactions. These benefits are thought to stem from the presence of more communication channels for the expression and reception of affiliative cues and the effortless processing of these cues. We investigated whether in-person versus phone-mediated interactions are characterized by higher accuracy of perceiving the other's affiliation and higher bias of assumed similarity with this other regarding affiliation. Using an event-contingent recording methodology, cohabitating romantic partners reported their perception of the other's affiliative behavior and their affiliative behavior in interactions with each other during a 20-day interval. Participants during in-person interactions (1) were more accurate in perceiving affiliative behavior and (2) assumed greater similarity between their own and their partner's affiliative behavior. Findings suggest that greater accuracy in perceiving affiliation and assumption of similarity with the romantic partner with respect to affiliation may in part explain the benefits of in-person interactions. Highlights: The accuracy of perceived affiliation was compared between in-person vs. phone interactions. Romantic couples reported their daily interactions with each other over 20 days. The accuracy of perceiving affiliation was higher when interacting in-person than over the phone. Partners assumed they were more similar with respect to affiliation when interacting in-person. Greater accuracy of perceived affiliation may in part explain the benefits of interacting in person.